Malawi : 2012 Article IV Consultation and Request for a New Arrangement Under the Extended Credit Facility: Staff Report; Staff Supplements; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Malawi. (IMF Staff Country Reports; Country Report, 2012)
The Malawian economy is slowly recovering, thanks to corrective measures such as the floating exchange rate regime and liberated current account transactions. Stringent fiscal discipline, restrained monetary policies, and boosting of international reserves have been suggested as measures for controlling inflation and stabilizing the macroeconomy. Operation power and freedom for results-based management (RBM) and implementation of Malawi Growth and Development Strategy II (MGDS-II) are also suggested by the Executive Board. Measures to ensure revenue gain concurrent with spending have also been recommended.